AREA DISTRIBUSI DAN VARIASI MORFOLOGI ULAR PUTIH (Micropechis ikaheka) DI PAPUA - Keliopas Krey (Jurnal Natural, 2009)
The objectives of the research were to identify the area of distribution and the specific habitat of the white snake (Micropechis ikaheka) in Papua (Western New Guinea), and to explain the morphological variation among the populations of that snake. About eight months of field work were taken to conduct the survey (April 2002; June 2006; and March to Augusts 2007) in several areas in the mainland and off-shore islands of Papua. Observation were carried out in the field at night and during the day to collect the snake. The studies were done on a collection of specimens that were found in the Museum Zoologicum Bogoriense LIPI in Cibinong, Conservation International in Jayapura and the Biology Laboratory of the Papua State University in Manokwari.The results showed that the white snake Micropechis ikaheka can be divided into three separate groups based on the color of the scales, i.e. Black, Brown and Yellow. The black one is the new group found in this research, and also there was one individual snake with transitional coloration between the brown group and the yellow group. However, M. Ikaheka is common and has a relatively wide distribution in New Guinea, but every group has a specific and limited area of distribution. The group with black color is distributed in the islands of Waigeo and Batanta and the group with yellow color is distributed from Manokwari, Sorong, upto the islands of Salawati, Batanta and Waigeo. Meanwhile, the brown colored sanke is distributed from the island of Yapen, mainland of Waropen, Mamberamo, Jayawijaya, Mindiptana up to Papua New Guinea.